ANALISIS APLIKASI MODEL HUJAN-ALIRAN UNTUK PENDUGAAN ALIRAN PERMUKAAN PADA VEGETASI LANTAI DAN SEMAK DI KAWASAN TAMAN MUMBUL - Ananda, Komang Dean; Udiyana, Bagus Putu; Sapanca, Putu Laksmi Yuli (Fakultas Pertanian Universitas Mahasaraswati Denpasar, 2019)
The function of vegetation is to reduce rain erosivity and surface flow by intercepting rainwater that falls on it. The surface of the land covered by vegetation will help the occurrence of rain interception. Rain interception is the retention of rainwater on the surface of the vegetation before water enters the soil or evaporates back into the atmosphere. The Mumbul Park area has grass and bush vegetation that can help interception so that it can maintain the availability of water in the soil and supply water discharge for several springs. The research was conducted in the Taman Mumbul area, Sangeh Village, Abiansemal District, Badung Regency, Bali Province. To estimate surface flow, the Rain-Flow Model Application method is used. From the results of the study, obtained an average runoff in flat land for grass growthform as much as 4,202 cc and shrubs as much as 4,083 cc, on sloping land in a row of 5,473 cc and 6,423 cc, and on sloping land as much as 16,443 cc and 12,325 cc. The waiting time for runoff growthform on flat land and shrubs are 20s and 22s respectively, sloping land 19s and 14s, and sloping land 11s and 10s. Groundwater content during the rainy season is 42.9%; 41.3%; 40.0%. The Taman Mumbul area has several springs with large debits, but during the dry season there is a decrease in spring discharge by 15% to 50%. Even though there is no drought during the dry season in the Mumbul Park area, the decline in the number of springs discharge is a warning to maintain ecosystem stability, especially the hydrological cycle.